Impact and adaptation of micro, small and medium enterprises in Ambon City during the Covid-19 Pandemic - Maryam Sangadji; Lussi R. Loppies (Institute of Computer Science (IOCS), 2023)
A MSMEs play an important role in labor absorption, and increasing community income. In its development, it has experienced ups and downs, besides covid-19, it has an impact on the existence of MSMEs which must be able to adapt in order to survive and continue to exist. The purpose of the study was to: determine the impact and adaptation of MSME actors in Ambon City during the Covid-19 pandemic. Through the qualitative method of phenomenology, the data revealed how the impact and adaptation of MSME actors in Ambon City. The results showed: there are six impacts felt due to Covid-19 on MSMEs, namely: (1) a decrease in income, (2) the proliferation of MSMEs, (3) strengthening data on MSME actors at the Office of Cooperatives and MSMEs, (4) increasing the skills of MSME actors, (5) capital assistance through the National Economic Recovery (PEN) program; and (6) strengthening the solidarity of social networks. Adaptations made by MSMEs during the pandemic are: (a) Reducing the amount of production; (b) Adjusting to new products/business diversification; (c) Expanding marketing points off line; (d) Marketing products through on line. This adaptation does not occur as a whole for all items for all business actors